MiRNA-22 Upregulates Mtf1 in Dorsal Horn Neurons and Is Essential for Inflammatory Pain. (10th February 2022) - Hao, Ling-Yun; Zhang, Ming; Tao, Yang; Xu, Hengjun; Liu, Qiaoqiao; Yang, Kehui; Wei, Runa; Zhou, Huimin; Jin, Tong; Liu, Xiao-Dan; Xue, Zhouya; Shen, Wen; et al.
Abstract : Chronic inflammatory pain seriously affects patients' quality of life because of a paucity of effective clinical treatments caused, at least in part, by lack of full understanding of the underlying mechanisms. miRNAs are known to be involved in inflammatory pain via silencing or degrading of target mRNA in the cytoplasm. The present study provides a novel mechanism by which miRNA-22 positively regulates metal-regulatory transcription factor 1 ( Mtf1 ) in the nuclei of neurons in the dorsal horn of the spinal cord. We found that miRNA-22 was significantly increased in the dorsal horn of mice with either inflammatory pain induced by plantar injection of complete Freund's adjuvant (CFA) or neuropathic pain induced by unilateral sciatic nerve chronic constrictive injury (CCI). Knocking down or blocking miRNA-22 alleviated CFA-induced mechanical allodynia and heat hyperalgesia, whereas overexpressing miRNA-22 produced pain-like behaviors. Mechanistically, the increased miRNA-22 binds directly to the Mtf1 promoter to recruit RNA polymerase II and elevate Mtf1 expression. The increased Mtf1 subsequently enhances spinal central sensitization, as evidenced by increased expression of p-ERK1/2, GFAP, and c-Fos in the dorsal horn. Our findings suggest that the miRNA-22– Mtf1 signaling axis in the dorsal horn plays a critical role in the induction and maintenance of inflammatory pain. This signaling pathway may be a promising therapeutic target in inflammatory pain.